L’universel et le particulier : enjeux et présupposes de la “littérature-monde” en français - Nicolas di Meo (Carnets)
On March 16th, 2007 a manifesto entitled “Pour une littérature-monde en français” (“Toward a World- Literature in French”) was published in the newspaper Le Monde. It was followed two months later by a collective book called Pour une littérature-monde. Both texts condemned French cultural nationalism (as well as the idea of French universalism) and criticized the notion of national literature, because this concept suggests the existence of a privileged relationship between one language (French) and one nation (France). According to most contributors to the book, only the experience of the local can lead to the universal. This idea, however, is not a new one. It was already a common representation in the first half of the 20th century. But in spite of this apparent continuity, huge differences remain, since the words “local”, “universal”, and “identity” have acquired new meanings. In terms of politics, Pour une littérature-monde uses the local/universal dialectic in various strategies aimed at denouncing French cultural imperialism.